Mental health effects on workers returning to work during the Covid-19 pandemic. An analysis of the maquiladora industry in northern Mexico - Máynez Guaderrama, Aurora (2022)
The aim of this research is to analyze the psychological effects caused by Covid-19 on the workers' readiness to return to work during the current pandemic. A cross-sectional study was designed that explored the perception of fear, work stress, and burnout in a sample of 333 workers belonging to the maquiladora industry in northern Mexico. The perceptions were gathered using a Likert scale survey of 5 points based on previously validated scales. The statistical technique used was the structural equation model (PLS-SEM). The results obtained reflect that the fear of Covid-19 influences directly the presence of stress and burnout in workers. It was demonstrated that burnout influences negatively and significantly the intention to return to work, however, no evidence was found that proves the negative effect of fear of Covid-19 on returning to work. We conclude that the pandemic is an event that affects the occupational health of the maquila workers, and it represents new risks in the performance of work due to workers' exposure. This situation generates fear, stress, and burnout, which finally affects the readiness to return to work, with its subsequent effects in terms of performance.